Isolation and characterization of a Bdellovibrio bacteriovorus from fish pond water - Hong, Qian-Ming; Yuan, Kai; Zhang, Meng-En; Yang, Xin-Rui; Chen, Qi; Xu, Shi-Wei; Chen, Wan-Yi; Qian, Shi-Xin; Miao, Yu-Tao; Zhu, Zhi-Ming; Chen, Yi-Hong (Frontiers in Microbiology, 2024)
IntroductionThe intricate habitats of aquatic organisms, coupled with the prevalence of pathogens, contribute to a high incidence of various diseases, particularly bacterial infections. Consequently, the formulation of sustainable and effective disease management strategies is crucial for the thriving aquaculture sector.Methods and resultsIn this investigation, a strain of Bdellovibrio bacteriovorus, designated B. bacteriovorus FWA, was isolated from a freshwater fish pond. Identification was achieved through microscopic examination of morphological characteristics, biochemical property assessment, and phylogenetic analysis. The lysogenic capability of B. bacteriovorus FWA was evaluated, revealing its effectiveness in lysing Escherichia coli, Aeromonas hydrophila, Vibrio alginolyticus, Vibrio parahaemolyticus, and Edwardsiella tarda. Physiological analysis indicated that the optimal ratio of B. bacteriovorus FWA to host bacteria was 1:10,000, with strict aerobic requirements. The optimal pH range for growth and reproduction was 7.0–8.0, the ideal temperature was found to be 30–35°C, with a preferred Na+ concentration of 0% and a Ca2+ concentration of 15–25 mM. Additionally, B. bacteriovorus FWA demonstrated enhanced lytic activity against bacteria in aquaculture effluent while effectively managing ammonia-nitrogen levels.DiscussionIn summary, B. bacteriovorus FWA holds significant promise for development as a probiotic agent in aquaculture.